2004
DOI: 10.1039/b403011g
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen in oxides

Abstract: The paper reviews the history and present understanding of protons in oxides; their defect chemistry, thermodynamics, and transport. Focus is put on correlations between hydration thermodynamics and other materials properties which may help to predict proton uptake and proton conduction in oxides. Also effects of defect association and the particular problem of high grain boundary resistance in high temperature proton conductors are addressed. In the second part, a number of experimental observations attribute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
352
4
2

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 380 publications
(383 citation statements)
references
References 37 publications
14
352
4
2
Order By: Relevance
“…Moreover, the apparent indications of hydride ions in the literature have now been rationalised by other, more credible phenomena, actually arising from transport of neutral hydrogen [2]. Therefore, it seems, at present, that hydride ions play no role in hydrogen permeation in oxides.…”
Section: What About Hydride Ions?mentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, the apparent indications of hydride ions in the literature have now been rationalised by other, more credible phenomena, actually arising from transport of neutral hydrogen [2]. Therefore, it seems, at present, that hydride ions play no role in hydrogen permeation in oxides.…”
Section: What About Hydride Ions?mentioning
confidence: 99%
“…Characterization of hydrogen permeation itself is more difficult as there are more sources of error and misinterpretation. It has been suggested that diffusion of neutral hydrogen species can be a major contributor to hydrogen permeationnot only in metals, but also in ceramics, to a larger extent than formerly anticipated [2]. Finally, framework materials with sub-nano-sized cages appear to provide interesting borderline cases between microporous hydrogen permeation and mixed ionic-electronic conduction [3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is in accordance with previous assumptions and recent ab initio calculations. 33,34 Formally, H O is a hydride and thus, similar to an oxide, has two valence electrons and an ionic radius of ca. 1.4 Å .…”
Section: A Thermodynamicsmentioning
confidence: 99%